Predictors of Cardiovascular Risk in Women. (September 2013) - Sallam, Tamer; Watson, Karol E
Cardiovascular disease is the leading cause of death in women, contributing to one in three female deaths. Despite improvements in overall cardiovascular outcomes, substantial gender and ethnic disparities remain. In order to improve outcomes among women, we recommend the following: every woman should undergo risk stratification for short-term and lifetime cardiovascular risk given the substantial long-term risk of cardiovascular disease; modifiable cardiovascular risk factors in women should be modified to the greatest extent possible; and these factors include lipid abnormalities, hypertension, smoking, diabetes, obesity, physical inactivity and, possibly, inflammatory markers. The rate of decline in heart disease is slower for women than men, highlighting the need for gender-specific interventions to address the outcomes gap.